The Social issue and the favela: State violence, pandemic, and working-class organization - Santos, Francine Helfreich Coutinho dos; Farage, Eblin; Pinto, Marina Barbosa (Argumentum, 2020)
Abstract: This text discusses daily life in the favelas, which is marked by State violence that, in the context of the Covid-19 pandemic, reiterates its class character. These are places where the destabilizing actions of the State are expressed - regarding social demands – while simultaneously imposing the presence of its armed forces under the rhetoric of maintaining order and controlling violence. The text presents the historic construction of the favelas in Rio de Janeiro; the everyday discussions, colored by the political presence of the State for “in”security; and some elements around the forms of resistance built by the working class sectors that live in the favelas. The methodology used is expressed along three axes: exploratory research to reach the proposed objectives, bibliographic review dialoguing with classic and contemporary authors, and qualitative research. Keywords: Favela. Pandemic. Workers’ organization.